Regulation Lawyers’ Ethics in Digital Litigation: Issues and Reforms on Access to Electronic Evidence (Lembaga Contrarius Indonesia, 2026)
The digitalization of Indonesia’s judiciary has generated new ethical challenges for the legal profession, particularly in relation to access and use of electronic evidence. Key concerns include potential breaches of data confidentiality, manipulation of digital evidence, and the absence of clear ethical standards governing advocates in e-court proceedings. Current procedural law and the advocates’ code of ethics do not adequately address the complexities of electronic evidence, which inevitably raise issues of privacy, cybersecurity, and procedural justice. This study aims to examine the ethical dilemmas faced by lawyers in digital litigation in Indonesia and to formulate both normative and institutional solutions to strengthen professional accountability. Employing normative legal research in statutory, conceptual, and philosophical approaches, supported by case analysis involving evidence, the study highlights a regulatory gap in the advocates’ code of ethics and deficiencies in ethical oversight mechanisms. Missed leading in legal practices, especially in the electronic court, where everyone can access electronic evidence to support the need for regulation to protect electronic evidence in the electronic court. The findings suggest the need for reform through the incorporation of specific standards on electronic evidence within the code of ethics, enhancement of lawyers’ digital literacy, and establishment of technical guidelines by professional organizations and the Supreme Court.